Relationship Between Height and Skeletal Malocclusion Type Using Steiner Analysis in The Banjar Ethnic Group: Cross Sectional Study - Kurniawan, Fajar Kusuma Dwi; Sitepu, Alexander; Dewi, Renie Kumala; Diana, Sherli; Fathonah, Zeni Dwi (Indonesian Dental Association, 2025)
Introduction: Indonesia is a country rich in ethnic diversity. Each tribe has characteristics that differ from other tribes. One of these differences lies in height, which is composed of long bones. The growth of long bones is the result of the ossification of cartilage located at the distal end. One of the long bones found in the craniofacial area is the mandible. The lateral cephalometric X-ray photos with Steiner analysis reveal the mandible's significant role in determining the type of skeletal malocclusion. Objective: This study aims to analyze the relationship between height and skeletal malocclusion type using Steiner analysis in the Banjar ethnic group. Methods: This research is a correlational analytical study with a cross-sectional design. The sample consisted of 62 Banjar students aged 15–18 years, selected using the purposive sampling technique. Height was measured using a microtoise and converted into a Height-for-Age Z-score (HAZ) based on WHO standards. Skeletal relationships were determined through Steiner analysis on lateral cephalometry using the SNA, SNB, and ANB angular parameters. Statistical analysis was performed using the chi-square test and Spearman's correlation test with a significance level of α=0.05. Results: Most samples had below-normal height, above-normal SNA, normal SNB, and above-normal ANB. The results of the Spearman's correlation analysis showed a significance value of 0.446. Conclusion: Most subjects had heights categorized as below normal based on the WHO Height-for-Age Z-score (HAZ), and the most common skeletal pattern found was Class II skeletal malocclusion with a tendency toward maxillary protrusion and mandibular position still within normal limits according to the SNA and SNB parameters. The results of the Spearman correlation test showed a significance value of 0.446 (p > 0.05), so it can be concluded that there is no statistically significant relationship between height and the type of skeletal malocclusion in Banjar adolescents aged 15–18 years. Height cannot be used as an indicator to predict the type of skeletal malocclusion in the study population. Keywords: Steiner analysis, lateral cephalometry, Banjar tribe, body height, skeletal malocclusion type.